Wilsonova choroba - Mareček, Z; Brůha, R (Vnitrni lekarstvi, 2013)
Wilsons disease is an autosomal recessive genetic disorder in which copper accumulates in tissues, especially in the liver and the brain. The genetic defect affects the P type ATPase gene (ATP7B). More than 500 mutations causing Wilsons disease have been described. The most common mutation in Central Europe concerns H1069Q. The symptoms of Wilsons disease include hepatic or neurological conditions. The hepatic condition is manifested as steatosis, acute or chronic hepatitis or cirrhosis. The neurological conditions are most often manifested after the age of 20 as motor disorders (tremor, speech and writing disorders), which may result in severe extrapyramidal syndrome with rigidity, dysarthria and muscle contractions. The dia-gnosis is based on clinical and laboratory assessments (neurological signs, liver lesions, low ceruloplasmin, increased free serum copper, high Cu volumes in urine, KayserFleischer ring). The dia-gnosis is confirmed by a high Cu level in liver tissue or genetic proof. Untreated Wilsons disease causes death of the patient. If treated properly the survival rate approximates to the survival rate of the common population. The treatment concerns either removal of copper from the body using chelating agents excreted into the urine (Penicillamine, Trientine) or limitation of copper absorption from the intestine and reducing the toxicity of copper (zinc, ammonium tetrathiomolybdate). In the Czech Republic, Penicillamine or zinc is used. A liver transplant is indicated in patients with fulminant hepatic failure or decompensated liver cirrhosis. In the family all siblings of the affected individual need to be screened in order to treat any asymptomatic subjects.
Keywords: transplantace jater; Zinc; hepatolentikulární degenerace; molybden; Copper; Česká republika; jaterní cirhóza; Cation Transport Proteins; mužské pohlaví; trientin; chelátory; mutace; Liver Cirrhosis; měď; penicilamin; Molybdenum; Adult; Czech Republic; Trientine; ženské pohlaví; adenosintrifosfatasy; Mutation; Humans; ATPasy transportující měď; Liver Transplantation; Hepatolenticular Degeneration; Copper-Transporting ATPases; zinek; Chelating Agents; Adenosine Triphosphatases; proteiny přenášející kationty; dospělí; Penicillamine; Female; lidé; Male